Infernal affairs trilogy [videorecording (Blu-Ray)] - Liu, Weiqiang, 1960-; Mai, Zhaohui, 1965-; Zhuang, Wenqiang; Lai, Yiu-fai; Ng, Man-ching; Chen, Guangrong, 1967-; Leung, Tony Chiu Wai, 1962-; Lau, Andy, 1961-; Lai, Leon, 1966-; Chen, Daoming; Chen, Huilin, 1973-; Wong, Anthony, 1965-; et al. (Criterion collection, 2022)
"Gripping saga of two rival moles--played by superstars Tony Leung Chiu-wai and Andy Lau Tak-wah--who navigate slippery moral choices as they move between the intersecting territories of Hong Kong's police force and its criminal underworld. Set during the uncertainty of the city-state's handover from Britain to China and steeped in Buddhist philosophy, these ingeniously crafted tales of self-deception and betrayal mirror Hong Kong's own fractured identity and the psychic schisms of life in a postcolonial purgatory."--Container.